2021
DOI: 10.1037/dev0001132
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in decision making under known risk: The role of working memory and impulsivity.

Abstract: This study examined whether age differences in risky decision making are dependent on known probability and value of outcomes (i.e., the expected value [EV]), the valence of anticipated outcomes (gains or losses), and individual differences in working memory and impulsivity. We used a task that varied risk independently from EV so that taking risks could be advantageous or disadvantageous. Results indicated differential developmental courses for the sensitivity to EV and outcome valence from early to late adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…For instance, 5–7 year old children do not systematically consider differences in expected value in risky choice when asked to choose between options with stated outcomes and probabilities, whereas children aged 8–11 years begin to approach the performance of adults (Levin et al, 2007 ). Such age-related differences in choice under known risk have been attributed to differences in working memory, suggesting that the ability to deal with described probabilities in making decisions is contingent on the maturation of cognitive control processes (Kray et al, 2021 ). More generally, understanding and executing described proportional calculations of probability appears to be a difficult skill for children to learn (Bryant & Nunes, 2012 ) and may require formal instruction.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 5–7 year old children do not systematically consider differences in expected value in risky choice when asked to choose between options with stated outcomes and probabilities, whereas children aged 8–11 years begin to approach the performance of adults (Levin et al, 2007 ). Such age-related differences in choice under known risk have been attributed to differences in working memory, suggesting that the ability to deal with described probabilities in making decisions is contingent on the maturation of cognitive control processes (Kray et al, 2021 ). More generally, understanding and executing described proportional calculations of probability appears to be a difficult skill for children to learn (Bryant & Nunes, 2012 ) and may require formal instruction.…”
Section: Discussionmentioning
confidence: 99%
“…However, Willoughby, Heffer, Good et al ( 2021 ) claimed that early adulthood is a period of more risk-seeking. Therefore, it is still unclear whether adolescents are more risk seeking than young adults (Kray et al, 2021 ). Moreover, adolescents tend to have a strong sense of belonging to peer groups (Blakemore, 2018 ), leading them to be more easily influenced by peers.…”
Section: Introductionmentioning
confidence: 99%
“…Willoughby, Heffer, Good et al ( 2021 ) found that early adulthood, rather than adolescence, might be the period of “high” risk-seeking in general and pointed out that future research should answer the question of “how different types of risky behaviors change at different ages and historical periods”. Therefore, based on these inconsistent findings from previous studies, it is necessary to explore whether adolescents are more risk seeking than young adults and the potential causes of these risky behaviors (Kray et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these abilities vary more from moment to moment, reflecting greater process fluctuations in these age groups (Li et al, 2004; Lindenberger & van Oertzen, 2006; Mella et al, 2016; Papenberg et al, 2013; Rutter et al, 2020). Second, prior research indicates that cognitive monitoring mechanisms operate less efficiently in childhood and old age than in early adulthood (e.g., Clawson et al, 2017; Dodson et al, 2007; Gajewski et al, 2018; Hämmerer et al, 2011; Kray et al, 2021; Schneider, 2008). Taken together, children and older adults show larger performance fluctuations from trial to trial, and are less precise in monitoring their performances over time.…”
mentioning
confidence: 99%